PERAN PERBEDAAN LABA YANG BERBASIS NILAI BUKU DAN PAJAK DALAM MENJELASKAN PERSISTENSI LABA (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - , ANNAS CAHYADI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study was to examine how the temporary differences between the book value and the taxes based income explain the persistence of earnings. First, this studty exemine and show differences provide additional information on the persistence of earnings. Then examine two potential causes of discrepancies income based on book value and taxes namely earnings management and tax planning. This study shows that the suspect and the differences in corporate income based on tax and book value derived from earnings management (EM subsample), earnings will be less persistent than other companies and the companies that the difference is caused by tax planning (TP subsample), earnings will be more persistent compared to other companies. This study also examined a more dominant factor in explaining differences in earnings on companies in Indonesia and found that the difference in earnings are more influenced by tax planning practice rather than earnings management